Avoiding cognitive inconsistency: Experimental evidence on sustainable online shopping - Jana Eßer; Daniela Flörchinger; Manuel Frondel; Stephan Sommer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Cognitive inconsistency, the discrepancy between individuals' behavior and their self-image, can cause the psychological discomfort called cognitive dissonance. In this paper, we investigate whether providing information that enhances the salience of cognitive inconsistency can increase sustainable consumption. Specifically, we analyze whether individuals avoid cognitive inconsistency by (a) a change in behavior to comply with own attitudes and by (b) the denial of attitudes and of knowledge about the criticism of conventional online shopping. To this end, we embed an incentivized discrete-choice task in a large-scale survey conducted in Germany in 2021, with the choice being between a voucher for either a conventional or a sustainable online market place. With our experimental setting, we aim to increase the salience of cognitive inconsistency by either randomly reminding participants of their previously stated attitudes towards sustainable production or by informing them about the typical criticism of conventional online shopping. Our empirical results indicate that individuals adapt their behavior after having received the reminder of their stated attitudes and the criticism about conventional online shopping. Yet, participants do not deceive themselves by aligning their attitudes with their behavior or by denying to have been aware of the criticism. – – Kognitive Inkonsistenz, d. h. die Diskrepanz zwischen dem Verhalten einer Person und ihrem Selbstbild, kann ein psychologisches Unbehagen hervorrufen, das als kognitive Dissonanz bezeichnet wird. In diesem Beitrag untersuchen wir, ob die Bereitstellung von Informationen, die die Bedeutung kognitiver Inkonsistenz erhöhen, den nachhaltigen Konsum steigern kann. Konkret analysieren wir, ob Individuen kognitive Inkonsistenz vermeiden, indem sie (a) ihr Verhalten ändern, um mit ihren eigenen Einstellungen übereinzustimmen, und (b) indem sie ihre Einstellungen und ihr Wissen über die Kritik am konventionellen Online-Shopping verleugnen. Zu diesem Zweck betten wir eine Discrete-Choice-Aufgabe in eine groß angelegte Befragung in Deutschland aus dem Jahr 2021 ein, bei der die Wahl zwischen einem Gutschein für einen konventionellen oder einen nachhaltigen Online-Marktplatz besteht. Mit unserem experimentellen Setting zielen wir darauf ab, die Salienz der kognitiven Inkonsistenz zu erhöhen, indem wir die Teilnehmenden entweder zufällig an ihre zuvor geäußerten Einstellungen zu nachhaltiger Produktion erinnern oder sie über die typische Kritik am konventionellen Online-Einkauf informieren. Unsere empirischen Ergebnisse deuten darauf hin, dass Personen ihr Verhalten anpassen, nachdem sie an ihre Einstellungen erinnert und über die Kritik am konventionellen Online-Shopping informiert wurden. Die Teilnehmenden täuschen sich jedoch nicht selbst, indem sie ihre Einstellungen mit ihrem Verhalten in Einklang bringen oder leugnen, von der Kritik gewusst zu haben.
Keywords: A13; H23; D91; 330; Behavioral economics; cognitive dissonance; sustainable behavior